Predictors of severity and functional outcome in natalizumab-associated progressive multifocal leukoencephalopathy. (May 2017) - Hoepner, Robert; Kolb, Eva M; Dahlhaus, Stefanie; Hellwig, Kerstin; Adams, Ortwin; Kleiter, Ingo; Salmen, Anke; Schneider, Ruth; Lukas, Carsten; Chan, Andrew; Berger, Joseph R; Gold, Ralf
Objective: Progressive multifocal leukoencephalopathy (PML) is an emerging complication of immunosuppressive therapies, especially natalizumab in multiple sclerosis (MS). Factors associated with functional outcome of natalizumab-associated PML (natalizumab-PML) have not been sufficiently described. Methods: We retrospectively analyzed medical records of all patients with natalizumab-PML ( n = 32) treated in our hospital since 2009. Disability measured by Expanded Disability Status Scale (EDSS) at two different time points (highest available EDSS during PML and last available EDSS after PML diagnosis) served as functional outcome parameters. Clinical, laboratory, and imaging data were analyzed for association with functional outcome by applying Spearman's rho and multivariate regression analysis. Results: In all, 31/32 patients survived PML. A poor functional outcome was associated with higher age, higher initial John Cunningham virus (JCV) copy number in cerebrospinal fluid (CSF), and more extensive PML lesions on initial magnetic resonance imaging (MRI). No association between functional outcome and the duration of natalizumab therapy or a delayed PML diagnosis was observed. Conclusion: This study will be useful for neurological practice to estimate functional outcome or disease severity of natalizumab-PML in primary care settings.